Acute serotonin 2A receptor blocking alters the processing of fearful faces in the orbitofrontal cortex and amygdala. (October 2013) - Hornboll, Bettina; Macoveanu, Julian; Rowe, James; Elliott, Rebecca; Paulson, Olaf B; Siebner, Hartwig R; Knudsen, Gitte M
Background: The serotonin 2A (5-HT2A ) receptor has been implicated in neural-processing of emotionally salient information. To elucidate its role in processing of fear and anger, healthy individuals were studied with functional magnetic resonance imaging (fMRI) after 5-HT2A receptor blockade, while judging the gender of neutral, fearful and angry faces. Methods: 5-HT2A receptors were blocked with ketanserin to a variable degree across subjects by adjusting the time between ketanserin-infusion and onset of the fMRI protocol. Neocortical 5-HT2A receptor binding in terms of the binding potential ( BPp ) was assessed prior to fMRI with 18 F-altanserin positron emission tomography (PET) and subsequently integrated in the fMRI data analysis. Also functional connectivity analysis was employed to evaluate the effect of ketanserin blocking on connectivity. Results: Compared to a control session, 5-HT2A receptor blockade reduced the neural response to fearful faces in the medial orbitofrontal cortex (OFC), independently of 5-HT2A receptor occupancy or neocortical 5-HT2A receptor BPp . The medial OFC also showed increased functional coupling with the left amygdala during processing of fearful faces depending on the amount of blocked 5-HT2A receptors. Conclusions: 5-HT2A receptor mediated signaling increases the sensitivity of the OFC to fearful facial expressions and regulates the strength of a negative feedback signal from the OFC to amygdala during processing of fearful faces.